On the system of strategic planning documents in the field of environmental protection and rational use of natural resources - L. V. Postulga (Гуманитарные и юридические исследования)
Introduction. The article discusses the problems of the system of strategic planning documents.   Materials and Methods. Within the framework of this research, the author analyzed the indicated problems using formal-legal analysis, synthesis, generalization, and comparative-legal methods, which allowed developing possible ways to solve them.   Analysis. The significance of the number of strategic acts regulated by law makes it difficult for strategic planning participants to understand the order and significance of actions performed within the framework of the planned process and the adoption of planned acts. The main goal-setting strategic document of the federal level in the field of socio-economic development has not been adopted. There is no correlation of goals and specific indicators in the planning acts of both one and different stages of planning. There are documents that are not regulated by the Law on Strategic Planning, but which, in turn, become the basis for the development of strategic documents on a downward vertical. The issues of defining uniform planning deadlines have not been settled. The absence of mechanisms for the implementation of planned acts and responsibilities has been revealed.   Results. Based on the analysis, proposals are put forward to improve the legal regulation of strategic planning, which will allow to build an effective system of strategic documents and ensure high efficiency of planned activities.